2018
DOI: 10.3389/fphar.2018.00202
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Ethylene Glycol)–Polylactide Micelles for Cancer Therapy

Abstract: For the treatment of malignancy, many therapeutic agents, including small molecules, photosensitizers, immunomodulators, proteins and genes, and so forth, have been loaded into nanocarriers for controllable cancer therapy. Among these nanocarriers, polymeric micelles have been considered as one of the most promising nanocarriers, some of which have already been applied in different stages of clinical trials. The successful advantages of polymeric micelles from bench to bedside are due to their special core/she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(68 citation statements)
references
References 112 publications
(121 reference statements)
0
68
0
Order By: Relevance
“…Poly(lactic Acid) (PLA) and Poly(lactic-co-glycolide) (PLGA) Copolymers. Among all the commonly used biodegradable synthetic polymeric (bio)materials, the most employed for drug delivery applications are the saturated poly(α-hydroxy esters), including poly(lactic acid) (PLA), poly(glycolic acid) (PGA), and poly(lactic-co-glycolide) (PLGA) copolymers [20][21][22][23][24]. Due to their excellent safety profile, good biocompatibility, low levels of immunogenicity and toxicity, and the tuneable rate of biodegradation in vivo, these polymers have been approved by the US Food and Drug Administration (FDA) and European Medicines Agency (EMA) as effective carriers for drug delivery in humans.…”
Section: Micelle and Vesicle Nanocarriers From Polymer-basedmentioning
confidence: 99%
“…Poly(lactic Acid) (PLA) and Poly(lactic-co-glycolide) (PLGA) Copolymers. Among all the commonly used biodegradable synthetic polymeric (bio)materials, the most employed for drug delivery applications are the saturated poly(α-hydroxy esters), including poly(lactic acid) (PLA), poly(glycolic acid) (PGA), and poly(lactic-co-glycolide) (PLGA) copolymers [20][21][22][23][24]. Due to their excellent safety profile, good biocompatibility, low levels of immunogenicity and toxicity, and the tuneable rate of biodegradation in vivo, these polymers have been approved by the US Food and Drug Administration (FDA) and European Medicines Agency (EMA) as effective carriers for drug delivery in humans.…”
Section: Micelle and Vesicle Nanocarriers From Polymer-basedmentioning
confidence: 99%
“…Moreover, self-assembly of amphiphilic block copolymers represents a versatile tool for the design of versatile nanocarriers for drug delivery applications. More specifically, the di-and tri-block copolymer of poly(ethylene glycol)/polylactide (PEG/PLA) systems, in the form of both polymer micelles and vesicles (polymersome), are attractive delivery systems since they are biodegradable with a good safety profile and sustained drug delivery [84,85]. The presence of the PEG on the nanocarrier shell prevents the unwanted adsorption of proteins and phagocytes, thereby increasing the period of the blood circulation, while the PLA hydrophobic core can efficiently encapsulate a variety of therapeutic agents [12,80].…”
Section: Amphiphilic Block Copolymersmentioning
confidence: 99%
“…biodegradable with a good safety profile and sustained drug delivery [84,85]. The presence of the PEG on the nanocarrier shell prevents the unwanted adsorption of proteins and phagocytes, thereby increasing the period of the blood circulation, while the PLA hydrophobic core can efficiently encapsulate a variety of therapeutic agents [12,80].…”
Section: Amphiphilic Block Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…28 This organic material has been successfully applied to vaccine development for infectious diseases and cancers. [29][30][31][32][33] However, recent studies have reported that a similar organic material, poly lactic-co-glycolic acid (PLGA), can also induce immune tolerance against the associated peptides for the treatment of autoimmune diseases, depending on particle size, shape, composition, and route of administration. 34,35 It was shown that tolerogenic effects require PLGA microparticle uptake by macrophages expressing the scavenger receptor MARCO and are, in part, mediated by the activity of regulatory T cells, abortive T-cell activation and T-cell anergy.…”
Section: Resultsmentioning
confidence: 99%